Very large SiPM arrays with aggregated output. (1st May 2022) - Razeto, A.; Acerbi, F.; Camillo, V.; Carlini, M.; Consiglio, L.; Flammini, A.; Galbiati, C.; Ghiano, C.; Gola, A.; Horikawa, S.; Kachru, P.; Kochanek, I.; et al.
Abstract: In this work we will document the design and the performances of a SiPM-based photo-detector with a surface area of 100 cm 2 conceived to operate as a replacement for PMTs. The signals from 94 SiPMs are summed up to produce an aggregated output that exhibits in liquid nitrogen a dark count rate (DCR) lower than 100 cps over the entire surface, a signal to noise ratio better than 13, and a timing resolution better than 5.5 ns. The module feeds about 360 mW at 5 V with a dynamic range in excess of 500 photo-electrons on a 100 Ω differential line. The unit can also operate at room temperature, at the cost of an increase of DCR to 10 8 cps.